WAYS TO INCREASE THE INCOME OF THE POPULATION DURING ECONOMIC TRANSFORMATION - Qulmatova D.Kh (TADQIQOTLAR, 2025)
Abstract: This article analyzes effective ways to increase the income of the population during economic transformation processes. It discusses key factors such as raising employment levels, encouraging entrepreneurship, introducing modern technologies, improving the investment climate, and developing vocational education. The article also reviews best practices from around the world, including the experience of Uzbekistan. Concrete proposals and recommendations are provided for diversifying sources of income and expanding social protection programs for the population.